(3JjSjQ GdJSjjQ GdeGdj ddeDSSI (B/s - (3HheOjf, jhSas ((3GdLRGFQ(B: s (3OGQ HdbjS(B, s, 2016)
(3WQM dfG gPG GdcJGH GdejRGfjI GdeGdjI habG ddeYGjjQ GdOhdjI ddeMGSHI,hJMdjdgG HGSJNOGe eDTQGJ GdJhGRf GdeGdj,eY bjGS GdCOGA HGSJNOGe MSGHGJ GdfJGFL h GdfSH GdeGdjI eY JjSjQ GdNRjfI HGSJYeGd LOhd GdJOabGJ, HGdGVGaI Edi LOhd GdJehjd hGdGSJKeGQ, hJjSjQ GMJjGLGJ QCS GdeGd GdYGed GdeYjGQj, hCNjQG GdJbjje GdeGdj ddeTGQjY GdGSJKeGQjI(B. s
(3eQGLY U(B.142 s
Keywords: (3GdEOGQI GdeGdjIs; (3GdeGdjI GdYGeIs